Pembangunan Model E-Learning di Perguruan Tinggi dengan Mempertimbangkan Faktor Kebutuhan Dinamis - Inayatulloh, Inayatulloh (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The purpose of this research is to build a model of a dynamic e-learning that can accommodate the needs of educational institutions. The research is performed with an analysis towards the observation of the learning activities in several higher education institutions. This method is carried out as a basis for creating models of dynamic e-learning comprehensive to meet the needs of students, lecturers and all parties concerned. The result achieved is a model of e-learning that can be used by universities in building and developing elearning applications.